Thin-film coating; historical evolution, conventional deposition technologies, stress-state micro/nano-level measurement/models and prospects projection: a critical review. (13th November 2019) - Mbam, Stephen Ogbonna; Nwonu, Sunday Emmanuel; Orelaja, Oluseyi Adewale; Nwigwe, Uzoma Samuel; Gou, Xiao-Fan
Abstract: Several modern cutting edge technologies, including the superconducting technology, green energy generation/storage technology, and the emerging 5G networks technology, have some form of thin-film coatings. Hence, this critical review showcased the historical evolution, conventional deposition technologies with its application areas, growth modes, specific thin-film stress-state micro/nano-level measurement and models, and prospects projection of thin-film coatings. Specifically, the authors included simple schematics of the primary thin-film coating methods (chemical vapor deposition and physical vapor deposition methods), growth modes, residual stress evolution behavior from valuable up to date models to enhance in-depth understanding of the underlying principles of thin-film coatings techniques and challenges. Also, the authors pointed out specific deficiencies in the reported thin-film stress measurement/models approaches. It is scientifically shown that no coating technique or model has superior results in all scenarios, selecting a suitable coating technique or model depends on the targeted materials and functions of the thin-film system. According to the evaluated reports, the societal demand and specific challenge in the fabrication/applications of thin-film systems indicated that thin-film coatings and its associated challenges would remain vibrant and active research areas for periods far into the future. Thus, this report would serve as a guide and reference material for potential researchers in these areas for a considerable time.